Development of a tractor-mounted kenaf harvesting machine - Musa, Dauda Solomon (2014)
The potential of kenaf (Hibiscus cannabinus L.) as an industrial commercial crop has been exploited in recent times. Kenaf harvesting operations are manually done or use other machinery for sugarcane. This makes harvesting difficult, time consuming and high labour cost and demand. A survey of kenaf harvesting machinery revealed that sugar cane harvesters and other machinery were either modified or adopted to harvest kenaf, hence field equipment for harvesting whole kenaf stems continues to be of interest in kenaf production. This necessitated the need to develop an efficient kenaf harvesting machine. This study focused on the development of a tractor-mounted kenaf harvesting machine to harvest whole kenaf stems which is either broadcast or rowplanted. In this regard a study on the physical and cutting characteristics of kenaf stem varieties FH 952 and V 36 revealed that the maximum plant height recorded was 310 cm and the lowest was 150 cm. Maximum stem diameter was 30 mm and the smallest was 14 mm. The moisture contents determined ranged between 73-75% (wet basis) for V 36 at harvest and 60.3-62.3% (wet basis) for FH 952. The cutting characteristics of kenaf stems at three different moisture content levels of 35%, 55% and 72% were also studied. The results revealed that the maximum cutting force and shearing energy were 1584.55 N and 8.75 J, respectively for 35% moisture content, while 694.86 N and 3.50 J were recorded for 72% moisture content. The Young’s modulus ranged between 67.59 MPa to 234.24 MPa. Laboratory experiments were conducted on cutting kenaf stem of variety V36 using a rotary serrated cutting system. The effects of cutting speeds on the cutting torque and cutting power of varying kenaf stem diameters and at different moisture contents and four different cutting speeds, 400 rpm, 500 rpm, 600 rpm and 700 rpm were investigated. Based on the experiments, the cutting speed had significant effect on the cutting power and torque. The cutting speed was directly proportional to the specific cutting power, while the cutting torque was inversely proportional to the moisture content. Increasing the rotational speed from 400 rpm to 700 rpm reduced the cutting torque from 1.91 Nm to 1.49 Nm. The cutting torque was observed to be higher at lower moisture levels of less than 35%. As the moisture content increased to values greater than 35%, the torque decreased considerably. This indicates that an increase in moisture content reduces cutting torque as shown by the model coefficient of moisture content, ct = 1.771 − 0.02mc. This means more energy savings and high efficiency would be achieved at high cutting speeds as compared to impact cutting system at similar speeds. Regression equations capable of predicting cutting torque and cutting power at varying stem diameters and cutting speeds, in relation to kenaf stem moisture contents are presented. After the aforementioned studies, a kenaf harvesting machine incorporating a rotary serrated cutting system was developed and its performance evaluated based on the physical and cutting properties studied. The kenaf harvester is tractor-mounted and comprises of a hydraulic, cutting and gathering systems. The parameters evaluated were the harvesting field efficiency (FE), effective field capacity (EFC) and machine material capacity (MC). Kenaf varieties V36 and FH 952 were used for the experiments to determine the performance of the machine. Different tractor speeds ranging from 2.0 to 7.7 km hr-1 were used. Field test results of the machine harvesting kenaf varieties V36 and FH 952 gave a harvesting field efficiency of 61 – 76%, effective field capacity of 1.19 – 3.68 ha/day and machine material capacity of 91.8 – 283.66 tons/day. The optimal operating forward speed at 3.7 km hr-1 achieved an efficiency of 76%. Results of the field test showed that the tractor speed had a significant effect on the performance of the machine, in terms of its effective field capacity, field efficiency and the machine material capacity. The machine performance revealed a satisfactory performance of the cutting system and it is suitable for harvesting kenaf stems of varying sizes. Total operational cost of the developed kenaf harvesting machine of RM 322,870.40/annum was compared with the common manual harvesting method of RM 13,500,000/annum widely practiced in Malaysia, and also the 4-row impact cutting kenaf harvesting machine of RM 416,636.00. The analysis showed that about RM13,177,129.60/annum will be saved when compared with the manual method and a saving of RM 93,765.60/annum when compared with the 4-row impact cutting kenaf harvesting machine.